Fuzzy multi criteria decision making applications: a review study - Asemi, A.; Baba, M.S.; Asemi, A.; Haji Abdullah, R.; Idris, N. (2014)
Fuzzy Multi Criteria Decision Making (FMCDM) techniques have a wide range of applications. However, they have different range of usage in various applications. In some applications they are more applied than others. In this study, we aim to investigate the most usage of FMCDM techniques among various applications. We select 150 articles that used FMCDM techniques for decision making. Then we analyzed the articles to investigate the application of FMCDM techniques. Finally, we found that “Location management” and “Supplier Selection” are the most applications for FMCDM techniques and among FMCDM techniques Fuzzy AHP and fuzzy TOPSIS are the most applied techniques.